Report of the Greater Montreal Community Development Initiative Steering Committee : Building Upon Change and Diversity within the English-speaking Communities of the Greater Montreal Region: - Greater Montreal Community Development Initiative (GMCDI) (Quebec Community Groups Network (QCGN), 2007)
In the 30 years since the passage of Bill 101, the nature of the English-speaking communities of the Greater Montreal Area has changed dramatically. The evolution of the largest linguistic minority within a linguistic minority in Canada has resulted in the emergence of certain unique challenges and opportunities. It was to address these issues that the Greater Montreal Community Development Initiative (GMCDI) was launched. This initiative, funded by the Department of Canadian Heritage, is intended to assist the English-speaking communities of the Greater Montreal Area in identifying shared community development challenges and priorities, and the most effective strategies to address them.
Keywords: Official Language Minority Community (OLMC)